Enhanced Antibacterial Potential of Fractionated Bioactive Compounds Isolated from Endophytic Nigrospora oryzae UILRZ1 in Ocimum gratissimum - Rahmat Folashade Zakariyah; Risikat Nike Ahmed; Kamoldeen Abiodun Ajijolakewu; Abdulmumeen Amao Hamid (Journal of Tropical Biodiversity and Biotechnology, 2025)
The recurring global health challenges due to antimicrobial resistance require an impulsive response to search for alternative drugs with strong activities against multidrug-resistant pathogens. This study evaluated and screened endophytic fungi of strong antibacterial potential from Moringa oleifera and Ocimum gratissimum. Primer pairs of ribosomal DNA's internally transcribed spacer regions (ITS1 and ITS4) were used to determine their evolutionary relationships. A principal component analysis (PCA) biplot was used to identify the most effective endophyte at a 95% confidence level (P˂0.05).  Improved culture conditions for the production of bioactive metabolites was done using the Taguchi design of experiment. Considering PCA biplot analysis, Nigrospora oryzae UILRZ1 from Ocimum gratissimum was most effective against selected pathogens. Production of metabolites was optimum at pH 5, 0.3 % (w/v) protein, 6-day inoculation time, and 4-plug inoculum, while variable of highest contribution was percentage of protein used. The column and thin layer chromatography were used to fractionate the extracts after optimization of production conditions while GCMS analysis was adopted to identify the chemical compounds. The crude extract's minimum inhibitory concentration (MIC) for chosen test microorganisms was 256 μg/mL prior optimization; while fractions of partially purified optimized extract of Nigrospora oryzae UILRZ1 showed enhanced antibacterial activity against Staphylococcus aureus with a MIC of 64 μg/mL. Efficient synthesis of bioactive metabolites was significant in the enhanced antibacterial activity against S. aureus.